Evolving Metalcore: Music Standardization and Commodification in Bad Omens and Bring Me The Horizon - Johny Alfian Khusyairi; Athaya Prita Belia (Jurnal Seni Musik, 2024)
This research aims to analyse the musical characteristics and lyrical themes of Bring Me The Horizon (BMTH) and Bad Omens to explore the cultural values shaped through the commodification of metalcore music, drawing on Adorno’s theory of the culture industry. This research uses mixed-methods approach by examining the duration of unclean and clean vocals, as well as the lyrical themes from both bands' debut and latest albums, to identify forms of standardization. In addition, the commodification analysis incorporates audience reactions, concert ticket sales, and streaming data. The findings reveal a transition from the creative freedom of the early years to more standardized works, marked by a reduction in unclean vocal techniques, less frequent use of blast beats, and a greater emphasis on smoother melodies. This study also identifies elements of pseudo-individualization, where both bands create a sense of uniqueness while adhering to market trends to appeal to a broader audience. These findings highlight how standardization and pseudo-individualization function not only as marketing tools but also as bridges to integrate metalcore music into the mainstream market and attract new listeners.